Use of a Model Aircraft for Rapid Low Cost Aerial Monitoring and Management of Forest Resources and Environment - Rathore, Chinmaya Singh (Indian Forester, 1999)
An attempt has been made to use a model airplane to take photographs that can be used for a wide range of forest management and environmental applications. The photographic platform is a small model plane used for hobby flying which has been fitted with an ordinary 35 mm camera which is triggered using a ground based FM transmitter. Initial results of a test flight over a forest area in Madhya Pradesh show a tremendous potential for generating a substantial amount of qualitative information that can prove immensely useful for monitoring and managing forest resources and areas of critical environmental concern. Extremely rapid acquisition of photographs coupled with phenomenally low costs suggest that the above technology can provide vital information inputs to forest and environmental managers in the country significantly enhancing conservation efforts.